2006
DOI: 10.1111/j.1540-8159.2006.00430.x
|View full text |Cite
|
Sign up to set email alerts
|

Anti‐Inflammatory Effect of Cardiac Resynchronization Therapy

Abstract: Although based upon a limited number of patients, this report indicates that CRT reduces peripheral markers of immune activation in patients with CHF. Further large scale studies are warranted to verify these findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(24 citation statements)
references
References 45 publications
2
20
2
Order By: Relevance
“…Data regarding the effect CRT on the concentration of proinflammatory cytokines have been conflicting. While some authors reported a decrease in proinflammatory cytokines (IL-6 and others) following CRT [13,14], other authors have not been able to confirm that finding [15,16]. In our study, the concentration of IL-6 decreased in CRT responders and remained unchanged in nonresponders.…”
Section: Discussionsupporting
confidence: 60%
“…Data regarding the effect CRT on the concentration of proinflammatory cytokines have been conflicting. While some authors reported a decrease in proinflammatory cytokines (IL-6 and others) following CRT [13,14], other authors have not been able to confirm that finding [15,16]. In our study, the concentration of IL-6 decreased in CRT responders and remained unchanged in nonresponders.…”
Section: Discussionsupporting
confidence: 60%
“…In clinical studies, cardiac resynchronization therapy has been shown to reduce interstitial remodeling, apoptotic cell death, and TNF-α expression [37]. Such decrease in inflammatory signals can attenuate post-infarct maladaptive signaling to native and transplanted cardiomyocytes, therefore providing a more conducive environment for regenerative therapy with stem cells to form more physiologically functional grafts [38].…”
Section: The Evidence For Electrical Stimulation To Promote a More Famentioning
confidence: 98%
“…It is speculated that CRT reduces inflammation, which could be one of the many factors responsible for an improvement in HF symptoms. A few small studies have looked at the effect of CRT on inflammation [9193], but they have been limited by either a small sample size or a short follow-up period. One of the larger studies [94] that followed 140 patients undergoing CRT over a median duration of 9 months showed that CRT-induced reverse remodeling (RR*) led to a decrease in inflammatory markers resulting in a reduction in adverse events.…”
Section: Biomarkers In Cardiac Resynchronization Therapymentioning
confidence: 99%